Degradation through Directional Self‐Doping and Homogeneous Density of Recombination Centers Hindered by 1, 8‐Diiodooctane Additive in Non‐Fullerene Organic Solar Cells. Issue 4 (1st March 2021) - Almora, Osbel; Wiegand, Julius; López-Varo, Pilar; Matt, Gebhard J.; Brabec, Christoph J.
Abstract : Non‐fullerene‐based organic solar cells (OSCs) have recently proven to perform with efficiencies above 18%. This is an important milestone for one of the most promising technologies in the fields of flexible and transparent/semitransparent photovoltaics. However, the stability of OSCs is still a challenging issue to meet the industry requirements. Herein, several devices with IT‐4F:PM6 as the active layer with and without 1, 8‐Diiodooctane (DIO) additive are characterized before and after a 1400 h degradation test under 1 sun white light‐emitting diode (LED) illumination intensity. The optoelectronic study via impedance spectroscopy under illumination at quasi‐open‐circuit correlates the use of DIO as an additive with a retarded degradation behavior and an overall improved device performance. In dark conditions, the Mott–Schottky analysis suggests that samples without DIO develop self‐doping during degradation, changing the p‐i‐n doping profile into a p–n type, most likely related to the evolution of the blend demixing. These mechanisms are further confirmed by drift‐diffusion simulations. Space‐oriented redistribution of shallow trap levels (self‐doping) and homogeneous increase in deep‐trap levels (nonradiative recombination) are shown to be hindered by the use of the DIO additive. Abstract : Non‐fullerene organic solar cells without 1, 8‐Diiodooctane additive are found to degrade with a self‐doping increase toward the interfaces, whereas the concentration of recombination centers homogeneously increase along the active layer. The study comprises monitoring current–voltage curves during in situ photostability tests, impedance spectroscopy under illumination at open‐circuit and in dark via Mott–Schottky analysis, and drift–diffusion numeric simulations.